Key technologies in telecom SD-WAN solution - Ye WANG (Dianxin kexue)
The basic concept of SD-WAN,application scenarios and the advantages in process of cloud network integration were introduced,and the key technologies of telecom SD-WAN solution were emphasized on,including open system architecture,rich deployment pattern,EVPN over VxLAN,traverse NAT,multicore soft-forwarding,etc.A solid foundation was established for the application of SD-WAN system.